2022
DOI: 10.3390/molecules27031041
|View full text |Cite
|
Sign up to set email alerts
|

Gelatin Coating for the Improvement of Stability and Cell Uptake of Hydrophobic Drug-Containing Liposomes

Abstract: Purpose: Most therapeutic agents have limitations owing to low selectivity and poor solubility, resulting in post-treatment side effects. Therefore, there is a need to improve solubility and develop new formulations to deliver therapeutic agents specifically to the target site. Gelatin is a natural protein that is composed of several amino acids. Previous studies revealed that gelatin contains arginyl-glycyl-aspartic acid (RGD) sequences that become ligands for the integrin receptors expressed on cancer cells.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Overall, our comprehensive XRD analysis underscores the promise of gelatin-coated CoFe 2 O 4 and MnFe 2 O 4 nanoparticles as viable candidates for targeted drug delivery applications, where the coating demonstrates favorable properties without compromising the underlying material's structural integrity. Moreover, the coating's role as a strain relaxer presents further opportunities for exploration in diverse biomedical settings ( Battogtokh et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, our comprehensive XRD analysis underscores the promise of gelatin-coated CoFe 2 O 4 and MnFe 2 O 4 nanoparticles as viable candidates for targeted drug delivery applications, where the coating demonstrates favorable properties without compromising the underlying material's structural integrity. Moreover, the coating's role as a strain relaxer presents further opportunities for exploration in diverse biomedical settings ( Battogtokh et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…In one notable study, FTIR analysis was utilized to study the interactions between the drug paclitaxel and a gelatin coating. The data revealed the formation of a protective layer around the drug, preventing its degradation and enhancing the stability of paclitaxel—an essential drug used in cancer treatment ( Battogtokh et al, 2022 ). Similarly, in another study, FTIR data was employed to study the controlled release of the drug insulin from a gelatin coating.…”
Section: Resultsmentioning
confidence: 99%
“…Proteins (albumin, gelatin, silk fibroin (SF), and others) used as liposome coatings and drug-binding molecules improved the long blood retention of the active compounds and sustained permeation along with a high capacity of controlled targeting [96,100,101].…”
Section: Coating Materials For Liposomes With Applications In Drug De...mentioning
confidence: 99%
“…8,10 Recently, new research revealed the presence of arginyl−glycyl−aspartic acid (RGD) sequences in Gel, which can act as a ligand for the targeting of overly expressed integrin receptors on some cancer cells, and Battogtokh et al showed the successful cell uptake of Gelcoated liposomes. 11 Gel is also among the widely available commercial products that can allow the liposomal system to be fabricated inexpensively. On the other hand, its synthesized counterparts PEG provide excellent control over physical and chemical capabilities like stimuli-responsive 12 or predicted distribution 8 and controlled release of drugs.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The technique of conjugation using electrostatic interactions is recognized as inexpensive and straightforward and thus can be applied for the purpose of simplistic coating for liposomes. 11 The synthesized Gel-based polymer will be examined at different ratios of 1:10, 1:50, 1:100, 1:200, and 1:500 (w/v) to liposome solution in order to find the optimal feeding quantity of this polymer as coating materials to liposomes. Following the synthesis processes, the materials are characterized structurally and analyzed qualitatively by Fourier transform infrared (FTIR), NMR, UV spectrometry, dynamic light scattering (DLS), differential scanning calorimetry (DSC), and thermogravimetric analysis Development of Gel-PEG-FA Coating to Liposomes.…”
Section: ■ Introductionmentioning
confidence: 99%